A new approach to determining the slip surface in tuff to determine the volume of landslide material: A case study on the West Sinjai road section, Sinjai Regency, South Sulawesi, Indonesia - Busthan, Busthan; Pachri, Hendra; Alimuddin, Ilham; Bahri, Syamsul; Bundang, Syarifullah (Brawijaya University, 2024)
Analysis of landslide slip surface based on the engineering properties of tuff rocks, including shear strength, water content, and infiltration rate on the West Sinjai road section, South Sulawesi, Indonesia. This study aimed to analyze the effect of shear strength, water content infiltration rate, and weathering grade of tufa rocks in the study area. The methods used in this study area included a study of weathered tuff profile characteristics, weathered tuff infiltration testing and residual soil (RS) determination of weathered tuff water content and residual soil, and testing of shear strength of weathered tuff and residual soil. This research used aspects of engineering geology, including shear strength, water content, and infiltration rate, as well as rock weathering grade to determine the slip surface in tuff to determine the volume of landslide material. The results showed that the tuff profile consisted of four grades, namely moderately weathered tuff (MW), highly weathered tuff (HW), completely weathered tuff (CW), and soil residual (RS). The rate of tuff infiltration increases with increasing weathering grade. The water content is more significant with the high degree of weathering of tuff. At the same time, the shear strength decreases with high weathering. Therefore, the research area is prone to landslide events. The slip surface is in a layer of moderately weathered tuff rock (MW), and those that experience landslides are highly weathered tuff rock (HW), completely weathered (CW), and residual soil (RS).